Reversibility of uranium and thorium binding on a modified bauxite refinery residue: The effects of aging temperature. (February 2015) - Clark, M.W.; Payne, T.E.; Harrison, J.J.; Comarmond, M.J.; Collins, R.N.; Reichelt-Brushett, A.J.
Abstract : Graphical abstract: Highlights: Th binds to MBRR irreversibly from pH 3 to 8, improving with temperature and time. 16–52% U binding is irreversibly bound, concentration and temperature dependent. U binding maximal at pH range, pH 5–6, but aging increases 232 U uptake at pH > 6. U and Th compete for similar sites affecting U binding cwf. simple 0.2 mM U aging. Increased U binding with aging is mostly from surface precipitate recrystallisation. Abstract: The effects of aging on the pH-dependence and reversibility of uranium and thorium binding by a modified bauxite refinery residue (MBRR) were studied in laboratory uptake/leaching experiments. Natural uranium and thorium isotopes (predominantly 238 U VI and 232 Th IV ) of 0.4, and 0.2 mM were loaded for an 8-day period at the natural equilibrium pH of the MBRR (approximately 8.5) and were allowed to age for 6 months in humid sealed containers at 4, 23, and 65 °C. After aging, anthropogenic 232 U VI and 229 Th IV were added as exchange isotopes and the pH decreased stepwise from 8 to 3 over several hours in pH dependent experiments. The relative concentrations of the isotope pairs (i.e. 238 U VI and 232 U VI ; 232 Th IV and 229 Th IV ) indicated that irreversibility of U VI and Th IV binding by the MBRR increased with aging and was dependent on the aging temperature and surface actinide loading. Linear combination fitting of the EXAFS data for the uranium loaded materials indicated that at low uranium concentrations sorption to minerals (particularly hematite) was a prime uranium removal mechanism, but at higher concentrations precipitation dominated. The data suggest that increased irreversibility and incorporation of U VI during aging is associated with re-crystallisation of precipitates.